EXPLORING ELECTRICAL ENGINEERING STUDENTS’ PERCEPTION TOWARDS ENGINEERING MATHEMATIC III IN UTHM - S. K. Yee,; M. F. Lee, (Online Journal for TVET Practitioners, 2018)
Engineering Mathematic III is a compulsory subject for the second years’ students in Faculty of Electrical and Electronic Engineering. Besides, it is also a pre-requisite subject for Electromagnetic Fields and Wave. It has been considered as one of the challenging subject amongst the bachelor courses in Electrical & Electronic Engineering programme. Therefore, students always facing problem to mastery this subject well and tend to fail this subject. Hence a case study through a survey method has been conducted to investigate the difficult subtopics in this subject. The survey also determined the problem facing by the students and their suggestions to overcome the obstacle to mastery this subject. A set of questionnaire through google form was used as instrument in this study. A purposive sampling technique was applied to select sample. About 14 students who are currently enrol in this subject and tend to have low score in the carry marks being selected as sample. Frequency and percentage were used to analyse the gather quantitative data, while the thematic analyses was applied to the gathered qualitative data. The findings shows that the 3 dimensional structure construction, triple partial integration and surface integral of vector field are the most challenging subtopics for the students. They must possess good imagination and basic mathematic in handling problems that involve many solution steps. They suggested that the lecturer should give additional exercises and punish the students if they do not complete the exercises. Students are satisfied with the current teaching method where the tutorial and lecture are allocated at different time slot in order to ensure their understanding for the subject content. Videos demonstrating of the solution step-by-step should be shared continuously and functioning as revision materials for students.